The impact of enteral immunonutrition on gut microbiota in colorectal cancer and gastric cancer patients in the preoperative period—preliminary results of randomized clinical trial - Kaźmierczak-Siedlecka, Karolina; Stachowska, Ewa; Kucharski, Robert; Wiśniewski, Piotr; Ulasiński, Paweł; Stańczak, Michał; Makarewicz, Wojciech; Skonieczna-Żydecka, Karolina; Kalinowski, Leszek (Frontiers in Immunology, 2025)
IntroductionImmunonutrition is a part of nutritional interventions in gastrointestinal cancer patients. It seems to be especially important in the preoperative period to reduce, among others, surgery-related complications. The relation between the immune system and gut microbiota has been previously analyzed. However, the influence of immunonutrients on the composition of gut microbiota is still unclear. Therefore, the aim of this study was to assess the impact of enteral immunonutrition on gut microbiota in gastric/colorectal cancer patients in the preoperative period.Patients and methodsThis study included 14 patients (n = 9 colorectal cancer, n = 5 gastric cancer) allocated to receive immunonutrition or standard products by 7 days prior to the surgery. Randomization was performed using a random number generator. The stool samples were collected at day 0 and after 7 days of consuming the study products. Therefore, gut microbiota analysis was conducted at the beginning and after 7 days (follow-up). The analysis consists of alpha diversity analysis, taxonomic data processing, beta diversity analysis, and differential abundance analysis.ResultsStatistical analysis did not indicate any significant differences (p > 0.05) between the two dietary groups for any of the alpha diversity indices. Microbial community compositions were largely similar between the immunodiet and standard nutridrink groups. Differential abundance analysis (DAA) using the Wilcoxon test identified several taxa with nominal p-values <0.05, suggesting potential differences in abundance between groups. However, none of these findings remained statistically significant. The taxa with nominal significance included Bilophila, CAG-56, Clostridium sensu stricto 1, Coprobacter, Holdemania, Fusicatenibacter, Ruminococcus, and [Eubacterium] eligens group.ConclusionsThe analysis of gut microbiota in the context of immunonutrition is a new area in oncology. In the current study, despite some initial microbial alterations, it was not finally confirmed that immunonutrition has a beneficial effect on gut microbiota in gastric and colorectal cancer patients in the preoperative period. However, the small sample size is one of the study’s limitations.